Improving Weather, Climate, and Hydrological Services Delivery in Central Asia - World Bank (World Bank, Moscow, 2016)
The purpose of this report is to present the results of an assessment of national weather, climate, and hydrological services in Central Asia and to present a program to improve these services. The report is based on the findings of three country assessments - the Kyrgyz Republic, the Republic of Tajikistan, and Turkmenistan - and supporting regional documentation. These and other countries that form the Central Asian region share common concerns, regarding economic development and the vulnerability of their economies and people to weather, climate, and hydrological extremes. National assessments are based on evaluations of weather, climate, and hydrological hazards; key users’ needs; national hydro meteorological services’ (NMS) capacities; and potential economic benefits from improvement of hydro meteorological service delivery. The results of this global facility for disaster reduction and recovery (GFDRR) work and summary report will contribute directly to the development of the regional initiative to improve weather, climate, and hydrological service delivery in the Central Asia.